Faeries, bears, and leathermen : men in community queering the masculine - Hennen, Peter (University of Chicago Press, 2008)
Over time, male homosexuality and effeminacy have become indelibly associated, sometimes even synonymous. In Faeries, Bears, and Leathermen, Peter Hennen contends that this stigma of effeminacy exerts a powerful influence on gay subcultures. Through a comparative ethnographic analysis of three communities, Hennen explores the surprising ways that conventional masculinity is being collectively challenged, subverted, or perpetuated in contemporary gay male culture. Hennen's colorful study focuses on a trio of groups: the Radical Faeries, who parody effeminacy by playfully embracing it, donning p.